Darwin‐Wallace Demons: survival of the fastest in populations of duckweeds and the evolutionary history of an enigmatic group of angiosperms. (26th March 2014) - Kutschera, U.; Niklas, K. J.
Abstract: In evolutionary biology, the term 'Darwinian fitness' refers to the lifetime reproductive success of an individual within a population of conspecifics. The idea of a 'Darwinian Demon' emerged from this concept and is defined here as an organism that commences reproduction almost immediately after birth, has a maximum fitness, and lives forever. It has been argued that duckweeds (sub‐family Lemnoideae, order Alismatales), a group containing five genera and 34 species of small aquatic monocotyledonous plants with a reduced body plan, can be interpreted as examples of 'Darwinian Demons'. Here we focus on the species Spirodela polyrhiza (Great duckweed) and show that these miniaturised aquatic angiosperms display features that fit the definition of the hypothetical organism that we will call a 'Darwin‐Wallace Demon' in recognition of the duel proponents of evolution by natural selection. A quantitative analysis (log‐log bivariate plot of annual growth in dry biomass versus standing dry body mass of various green algae and land plants) revealed that duckweeds are thus far the most rapidly growing angiosperms in proportion to their body mass. In light of this finding, we discuss the disposable soma and metabolic optimising theories, summarise evidence for and against the proposition that the Lemnoideae (family Araceae) reflect an example of reductive evolution, and argue that, under real‐world conditions (environmental constraints and other limitations), 'Darwin‐Wallace Demons' cannot exist, although the concept remains useful in much the same way that the Hardy–Weinberg law does.